Socio-economic determinants of crime rate in Malaysia - Tan, Hui Chen (Universiti Malaysia Sarawak (UNIMAS), 2016)
The study is to investigate the relationship between total crimes and real GDP per capita, unemployment rate, population growth and fertility rate in Malaysia by using the annually data which covered the period from year 1976 to year 2014. Augmented Dickey-Fuller (ADF) test, Philips and Perron (PP) test and Kwiatkowski-Philips-Schmidt-Shin (KPSS) test is to test the stationary properties of the variables. Johansen and Juselius co-integration and vector error correction model (VECM) were applied to examine the long run relationship together with causality relationship among the variables. Granger causality test was applied to find out the short run causality among the variables. The results imply that the variables are stationary at order one, I(1). Besides, Johansen-Juselius co-integration test also shows the existence of long-run relationship between the variables. Unidirectional Granger causality is running from GDP per capita, population and fertility rate to unemployment and bidirectional Granger causality between population and fertility rate. However, there is no short-run causality relationship between total crime rate and explanatory variables. Policy may focused on these socio-economic variables which might indirectly affect the crime rate in Malaysia.